Nanostructured Poly(methyl Methacrylate)-Silica Coatings for Corrosion Protection of Reinforcing Steel - Uvida, Mayara Carla [UNESP] (2022)
In the absence of preventive maintenance, corrosion of structural steel by the deterioration of the passive layer due to exposure to aggressive environments is the main failure factor of reinforced concrete. To overcome economic, safety, and environmental implications, present research efforts focus on eco-friendly organic-inorganic hybrid coatings to achieve effective protection of reinforcing steel. Nanostructured PMMA (poly(methyl methacrylate))-silica coatings developed by combining reactions of the polymerization of methyl methacrylate and 3-[(methacryloxy)propyl]trimethoxysilane with the sol-gel hydrolytic condensation of tetraethyl orthosilicate using isopropanol as a solvent represent a promising approach to accomplish this goal. The nanoscale dispersion of silica nodes covalently conjugated with PMMA chains led to transparent, homogeneous, and pore-free coatings deposited with a thickness of 15 μm on 2D and 3D reinforcing steel. Mechanical, thermal, and surface analyses showed a strong adhesion of the coating to the substrate surface (15.9 MPa), a thermal stability of up to 256 °C, and a contact angle of about 75°. Electrochemical assays in standard 3.5 wt % NaCl solution, simulated carbonated, and alkaline concrete pore solutions confirmed effective corrosion protection, with an impedance modulus of up to 100 Gω cm2(at 4 mHz) and a lifetime of more than 670 days. Hence, PMMA-silica hybrid coatings are an eco-friendly and efficient alternative to protect reinforcing steel against corrosion, helping to prevent structural failures and fatal accidents.